2021
DOI: 10.1088/1361-6463/abe9e0
|View full text |Cite
|
Sign up to set email alerts
|

Universal nature and specific features of streamers in various dielectric media

Abstract: In this paper, a review of general and specific properties of ionization waves—streamers is presented. Characteristics of streamers in gases and liquids, sprites in the Earth’s atmosphere and guided streamers in cold atmospheric-pressure plasma jets are discussed. Information on streamer structure, propagation velocity and radius, parameters of the streamer plasma (electron density in the streamer channel, peak electric field in the streamer head) in various media, obtained using diagnostic methods, numerical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 136 publications
7
26
0
Order By: Relevance
“…Recently, several experimental and numerical studies in point-to-plane geometry in air gaps of about 1 cm at atmospheric pressure have reported images of axisymmetric diffuse discharges with maximum radius of several centimeters as reviewed in Naidis et al (2018) and shown since then in Brisset et al (2019); Chng et al (2019); Tarasenko et al (2020); Tarasenko (2020); Chen et al (2020); Bourdon et al (2020); Babaeva and Naidis (2021); Zhu et al (2021). These discharges are obtained using high voltage pulses (with maximum voltages being five or ten times higher than classical steady-state breakdown levels) applied with sub-nanosecond and nanosecond rise times.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, several experimental and numerical studies in point-to-plane geometry in air gaps of about 1 cm at atmospheric pressure have reported images of axisymmetric diffuse discharges with maximum radius of several centimeters as reviewed in Naidis et al (2018) and shown since then in Brisset et al (2019); Chng et al (2019); Tarasenko et al (2020); Tarasenko (2020); Chen et al (2020); Bourdon et al (2020); Babaeva and Naidis (2021); Zhu et al (2021). These discharges are obtained using high voltage pulses (with maximum voltages being five or ten times higher than classical steady-state breakdown levels) applied with sub-nanosecond and nanosecond rise times.…”
Section: Introductionmentioning
confidence: 99%
“…So far, the number of experimental and numerical studies on positive diffuse discharges in atmospheric pressure air remains limited (Naidis et al, 2018;Tardiveau et al, 2009;Pechereau et al, 2014;Babaeva and Naidis, 2016b;Babaeva and Naidis, 2016a;Marode et al, 2016;Tardiveau et al, 2016;Tarasenko et al, 2020;Chen et al, 2020;Bourdon et al, 2020;Babaeva and Naidis, 2021;Zhu et al, 2021). Rather good agreement between experiments and simulations has been obtained on discharge characteristics such as the maximum discharge radius and ionization front velocity as reviewed in Naidis et al (2018); Babaeva and Naidis (2021) and on the time evolutions of the electric field on the symmetry axis as shown at very early times of discharge propagation in Brisset et al (2019) and during the whole discharge propagation in the gap in Bourdon et al (2020); Zhu et al (2021). As demonstrated for plasma jets in Xiong et al (2012); Lietz and Kushner (2018), the geometry of electrodes and the location of grounded surfaces around the studied set-up has a major influence on discharges at atmospheric pressure.…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that this resolution can be easily tuned by imaging optics and pixel binning. The proposed system can be helpful to characterize plasmas which have small plasma size of a few mm or steep gradients [4,8,[30][31][32][33][34][35]. Note that the capability to extend 1D measurement is also highly useful to diagnose larger scale test articles as well.…”
Section: Discussionmentioning
confidence: 99%
“…The added advantage of experimenting at reduced pressure is that the observer is essentially zooming in, both spatially and temporally, to the streamer discharge, following the scaling laws described by Ebert et al [15]. Our reduced electric field profiles determined for synthetic air are compared with numerical results obtained by Babaeva and Naidis [16] and Li et al [17]. Moreover, we apply a spectral fitting procedure to obtain the distributions of rotational and vibrational temperatures in the streamer head and tail with similar resolution, which is directly compared to the numerical simulation presented in this work.…”
Section: Introductionmentioning
confidence: 88%